Proceedings of the 6th Workshop on Argument Mining 2019
DOI: 10.18653/v1/w19-4515
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Scientific Elements for Text Similarity in Biomedical Publications

Abstract: Rhetorical elements from scientific publications provide a more structured view of the document and allow algorithms to focus on particular parts of the text. We surveyed the literature for previously proposed schemes for rhetorical elements and present an overview of its current state of the art. We also searched for available tools using these schemes and applied four tools for our particular task of ranking biomedical abstracts based on text similarity. Comparison of the tools with two strong baselines show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…We recently published a study in which we compared four tools for the extraction of the zones and evaluated them on seven use studies (https://github.com/mariananeves/scientific-elements-text-similarity) [5]. Our study also demonstrated that using pre-selected zones, instead of the whole abstracts, yields better performance in the ranking task.…”
Section: The Web Applicationmentioning
confidence: 78%
See 1 more Smart Citation
“…We recently published a study in which we compared four tools for the extraction of the zones and evaluated them on seven use studies (https://github.com/mariananeves/scientific-elements-text-similarity) [5]. Our study also demonstrated that using pre-selected zones, instead of the whole abstracts, yields better performance in the ranking task.…”
Section: The Web Applicationmentioning
confidence: 78%
“…However, given that not all abstracts in PubMed are structured, we automatically extract the zones for the remaining articles using the ArguminSci tool [6]. This was the best performing tool according to our study [5].…”
Section: The Web Applicationmentioning
confidence: 99%
“…Thus far, we have identified 15 `critical´ semantic types and have projected them onto a `master chart´. Futhermore, "zoning" of abstracts and elimination of sections that focus on methodology during preprocessing may also improve the selection of `relevantṕ ublications in the hitlist, by reversing any `negative selection´ due to alternative methodology (27).…”
Section: Discussionmentioning
confidence: 99%
“…The scientific entities or elements exploited by us to consider the `equivalence´ of biomedical research are essentially different from the ones used by other groups to distinguish research. Please see (10) for a comprehensive survey of such elements and annotated corpora Furthermore, we wondered whether it would be possible, to assign individual `critical´ scientific elements (i.e. original words from abstracts) to semantic types of the Unified Medical Language System (UMLS) semantic network (11) that would be generally `critical´ for any analysis of equivalence´ in the biomedical domain (e.g.…”
Section: Introducing the Smafira Projectmentioning
confidence: 99%
“…Rhetorical Structure Theory [15] describes discourse coherence relations. For mining scientific abstracts and full-text articles, researchers have developed a variety of types of text classification schemes described as rhetorical, e.g., see the survey in [17]. But none of the above is concerned with rhetorical analysis in the sense of this proposal, which is informed by computational and classical rhetoricians.…”
Section: Related Workmentioning
confidence: 99%